Pengaruh Fundamental Makro, Fundamental Mikro, Struktur Kepemilikan, Struktur Modal Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar Di BEI tahun 2020-2022 - Amru Karim Alhabsyi; Hwihanus Hwihanus (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to examine and analyze the influence of Macro Fundamentals, Micro Fundamentals, Ownership Structure and Capital Structure on Company Value with Financial Performance as an Intervening Variable in Food and Beverage Subsector Companies Listed on the Indonesian Stock Exchange in 2020-2022. The population in this study was 30 food and beverage subsector companies listed on the Indonesian Stock Exchange. The method used in this research is random sampling with a sample size of 15 companies. The data analysis technique in this research uses the Smart PLS (Partial Least Square) program version 4. The research results showed that of the 13 hypotheses created, 6 hypotheses were accepted and 7 hypotheses were rejected. Financial performance as four intervening variables also has insignificant results.